Parents find community: youth sports as a mobile neighborhood. Issue 11 (2nd November 2022) - Bjork, Christopher; Hoynes, William
Abstract: This article examines the impact travel sports have on adult participants. Parents of travel team players are expected to attend team meetings, be present at practices and training sessions year-round, and chaperone their sons and daughters to tournaments that may take place hours from their homes. As a result of the significant amount of time parents invest in their children's sports activities, other travel team parents often become a social anchor of their lives. Our analysis of youth sports parents highlights the sense of satisfaction that many adults from what is, on the surface, a child-centered activity, and also explores the difficulties faced by parents who are not eager to devote their social lives to the travel team. Understanding the social bonds that develop among youth sports parents helps to explain the often intense commitment many adults make to their children's sports teams.